A magia entre os critãos-novos - Santana, Nilton Bruno Feitosa (2015)
Kabbalah, the Jewish mystical practice born in the Middle Ages that has raised interest of the brightest minds of the Renaissance, being present among Jews and Gentiles will also be present in the New Christian means Judaizing. The intention of this research aims to highlight that even the Jews have been expelled and forced to convert to Catholicism in Spain (1492) and later in Portugal (1496), his descendants, the New Christians, developed a new type of Judaism in the midst of persecution, in which the Kabbalah became increasingly active. Kabbalah which was eventually called by the Inquisition as mere witchcraft, was propagated by the New Christians within your Crypto, a hidden Judaism, secret, in which Kabbalah was taking different formats, so you survived persecution. The cases studied show that although they were condemned by the Inquisition, mystical rituals were widely practiced in the Iberian Peninsula. Individuals of different faiths and social classes, the Kabbalah practitioners, were essential to the strength of the New Christian Judaizing culture.